PELAKSANAAN PENGELOLAAN ATRAKSI GAJAH DI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM KECAMATAN MINAS KABUPATEN SIAK - Alfy Syahri; Andi M. Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to determine how the implementation of the management of elephant Things Taman Hutan Raya Sultan Syarif Hasyim Siak District of Minas. This research used descriptive qualitative method to examine problems in the lift. In this study, researchers used three (3) key informant, key informant or infoman key is people who know the ins and outs of the phenomenon under study. then In the study the researchers also used an additional informant that there are four (4) additional informant that is used by researchers to supplement the information carefully.While data collection techniques in this study using interviews, observation, and documentation.Based on the research that has been done, the response of speakers that in Elephant Training Center Minas has a human resources / trainers, paramedics, biological resources / fauna, Stake holder, Travelers / consumer, Region / area, boundaries area, Animal protection , Wildlife animals. but it is still effective and the maximum is still due to land disputes and no permission from the Ministry of forestry Riau Province. Besides, the lack of interest from outside parties or private individual investors to further develop the potential that exists in this Minas PLG.Keywords: managing the elephant Attractions, Attractions, Elephant Training Center, District Minas